2 researchers won gold medals at Archimedes Russia - Noor Syahidah, Sabran
Universiti Malaysia Pahang (UMP) continued to strike gold at the international level when it won two gold medals in the 16th International Salon of Invention and Innovation Technologies (ARCHIMEDES) held at Sokolniki Exhibition Center in Moscow, Russia on April 5, 2013.